2019
DOI: 10.1016/j.mgene.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin-6 rs1800796 polymorphism with reduced cognitive performance in healthy older adults

Abstract: With increasing life expectancy, age-associated cognitive impairment is an escalating problem worldwide. Inflammation is one of the features that characterises cognitive decline and can stimulate neurodegeneration. Interleukin 6 (IL-6) is a cytokine frequently associated with a pro-inflammatory phenotype and increased levels have been associated with the pathogenesis of dementia. The rs1800796 polymorphism in the promoter region of IL-6 gene was previously shown to influence IL-6 expression and therefore we hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…77 The effect of G allele of rs1800796 on IL6 transcriptional activity and expression level unfortunately remained controversial. [78][79][80][81][82] The current meta-analysis reported association between G allele of rs1800796 with periodontitis ( Table 3) Indeed, a meta-analysis published in 2013 analyzed eight reports on rs1800796 and periodontitis indicated that the SNP might be associated with increased risk of periodontitis in Europeans. 21 Interestingly, frequencies of G allele at rs1800796 appeared very different among the two Caucasian studies, being 5% 48 or 94%.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…77 The effect of G allele of rs1800796 on IL6 transcriptional activity and expression level unfortunately remained controversial. [78][79][80][81][82] The current meta-analysis reported association between G allele of rs1800796 with periodontitis ( Table 3) Indeed, a meta-analysis published in 2013 analyzed eight reports on rs1800796 and periodontitis indicated that the SNP might be associated with increased risk of periodontitis in Europeans. 21 Interestingly, frequencies of G allele at rs1800796 appeared very different among the two Caucasian studies, being 5% 48 or 94%.…”
Section: Discussionmentioning
confidence: 74%
“…The effect of G allele of rs1800796 on IL6 transcriptional activity and expression level unfortunately remained controversial 78‐82 . The current meta‐analysis reported association between G allele of rs1800796 with periodontitis (Table 3).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation